An affair of state : the investigation, impeachment, and trial of President Clinton - Posner, Richard A. (Harvard University Press, 1999)
In a book written while the events were unfolding, Richard Posner presents a balanced and scholarly understanding of President Clinton's year of crisis which began when his affair with Monica Lewinsky hit the front pages in January 1998. With the freshness and immediacy of journalism, Posner clarifies the issues involved, carefully assesses the conduct of Independent Counsel Kenneth Starr, and examines the pros and cons of impeaching President Clinton as well as the major procedural issues raised by both the impeachment in the House and the trial in the Senate. This book, reflecting the breadth of Posner's experience and expertise, will be the essential foundation for anyone who wants to understand President Clinton's impeachment ordeal.